2019
DOI: 10.1007/s42380-019-00017-7
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Reasons for Why They Were Targeted for In-School Victimization and Bullying

Abstract: The efficacy of youth violence prevention policies, programs, and practices partly depends on understanding the reasons for why students are targeted for victimization. However, what is known about why some students are targeted for victimization over others is limited to researcher-generated reasons and therefore may risk ecological validity. This study used a qualitative opencoding content analyses to make sense of 8531 students' open-ended responses about the reasons why they were targeted for victimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(66 reference statements)
1
7
1
1
Order By: Relevance
“…These findings offer support to research demonstrating links between personality, behaviour and bullying (e.g. Bosacki, Marini, and Dane 2006;Warrington and Younger 2011;Gardella et al 2020), but also illustrate that someone may be bullied for being too quiet or not quiet enough, or for being too shy or too playful. This highlights the importance of the social context of bullying relations, wherein the bodies that students bring to social situations are categorically identified and located within a social structure (Goffman 1990), and illustrates the relevance of dominant normative orders (Ellwood and Davies 2010).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These findings offer support to research demonstrating links between personality, behaviour and bullying (e.g. Bosacki, Marini, and Dane 2006;Warrington and Younger 2011;Gardella et al 2020), but also illustrate that someone may be bullied for being too quiet or not quiet enough, or for being too shy or too playful. This highlights the importance of the social context of bullying relations, wherein the bodies that students bring to social situations are categorically identified and located within a social structure (Goffman 1990), and illustrates the relevance of dominant normative orders (Ellwood and Davies 2010).…”
Section: Discussionsupporting
confidence: 78%
“…Walton, 2011; Horton 2019) by drawing attention to the ways in which people are located within a 'cross-cutting grid' of social structures (Goffman 1983, 14). While Gardella et al (2020) only found a few cases where social structures were put forward by participants as a reason for why they were bullied, our study found such reasoning to be more commonplace. For example, explanations dealing with opinions illustrate the links between bullying and broader social structures and how someone may be bullied for being perceived as anti-racist or racist, or proor anti-LGBT rights.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Being 'a teachers' pet' might well be a reason for becoming a target of bullying. Gardella et al (2019) stated that if students were favoured by teachers, they were more likely victimised. Santinello et al (2010) found an association between bullying and teacher unfairness was found with students who bullied others but not with victims of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kim and Choi (2021), cyberbullying in the workplace may involve a power imbalance between the parties in which the target is unable to defend themselves, such as supervisors bullying their subordinates. Along the same lines, Gardella et al (2019) argue that lowwage workers are more vulnerable to workplace harassment and violence and that these workers almost never seek justice against their violators.…”
Section: The Risks Of Cyber Bullying In the Workplacementioning
confidence: 99%